2016
DOI: 10.1002/chem.201602007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Bottom‐Up Preparation of Graphene Nanoribbons by Mild Suzuki–Miyaura Polymerization of Simple Triaryl Monomers

Abstract: Herein an efficient bottom-up solution-phase synthesis of N=9 armchair graphene nanoribbons (GNRs) is described. Catalyzed by Pd(PtBu3 )2 , Suzuki-Miyaura polymerization of a simple and readily available triaryl monomer provides a novel GNR precursor with a high molecular weight and excellent solubility. Upon cyclodehydrogenation, the resulting GNR exhibits semiconducting properties with an approximately 1.1 eV band gap (LUMO: -3.52 eV; HOMO: -4.66 eV) as characterized by UV/Vis-NIR spectroscopy and cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 43 publications
(31 reference statements)
8
49
0
5
Order By: Relevance
“…[125] Thea uthors observed that the formation of the first four bonds is very fast (Figure 10 (Figure 10). [126][127][128][129] In the case of the hexafluorenylfused HBC 143,D DQ/MsOH proved to be more efficient than FeCl 3 (28 %versus 18 %yield). [128] As aconsequence of the presence of twelve hexyl chains pointing out of the PA H plane,t he aggregation of 143 in solution is restricted and it shows good solubility in common organic solvents.…”
Section: Large Planar Pahs Expanded Acenes and Nanographenesmentioning
confidence: 99%
“…[125] Thea uthors observed that the formation of the first four bonds is very fast (Figure 10 (Figure 10). [126][127][128][129] In the case of the hexafluorenylfused HBC 143,D DQ/MsOH proved to be more efficient than FeCl 3 (28 %versus 18 %yield). [128] As aconsequence of the presence of twelve hexyl chains pointing out of the PA H plane,t he aggregation of 143 in solution is restricted and it shows good solubility in common organic solvents.…”
Section: Large Planar Pahs Expanded Acenes and Nanographenesmentioning
confidence: 99%
“…The classical solution synthesis has provided a variety of GNRs with different structural features and tunable band gaps, and can afford GNR materials on a gram scale, which can be processed from a solution for physical characterization and device fabrication [127,[139][140][141][142][143]. However, proving the structural perfection of such large macromolecules at the atomic level remains a challenging task.…”
Section: Vivacity Of Pah Chemistry In Light Of Gnrs and Graphenementioning
confidence: 99%
“…In contrast, there is an obvious lack of knowledge about their optical properties. Optical absorption spectroscopy has been reported, showing the dependence of the gap on the width of the GNR [12,14,[20][21][22]. The comparison between reflectivity measurements on GNRs grown on gold and ab-initio calculations recently highlighted the excitonic nature of the optical transitions, with exciton binding energy as high as 1.5-1.8 eV [23].…”
Section: Introductionmentioning
confidence: 99%